Gamifying Reading: Using Quizizz to Boost EFL Students’ Narrative Text Skills - Qomariyah, Nilam Lailiyatul; Taufiq, Wahyu (Jurnal Metaedukasi: Jurnal Ilmiah Pendidikan, 2025)
This study aims to examine the effectiveness of using the Quizizz application with gamification techniques to improve students' reading comprehension, particularly in understanding narrative texts. The research employed a quasi-experimental design involving two classes at a scool in Sidoarjo, East Java. The experimental group used Quizizz as a learning medium, while the control group used conventional teaching methods. The results showed a significant improvement in reading comprehension in the experimental group compared to the control group. The application of gamification elements such as points, avatars, leaderboards, and instant feedback successfully increased students’ motivation, engagement, and learning outcomes. These findings indicate that integrating technology-based gamified learning tools like Quizizz can be an effective strategy for improving students’ reading comprehension in English, especially in narrative texts.